MENGINISIASI ASURANSI PERDAGANGAN KARBON SYARIAH - Muhammad Musa (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
Sharia insurance can play an important role in supporting carbon trading and managing risks related to climate change, for example, from the seller's side, insurance can protect the business activities of private parties or governments that carry out carbon sequestration. For example, forest replanting insurance, renewabelle energy, and so on. Then insurance and reinsurance companies can also play a role on the buyer's side. However, because buyers are carbon emitters, incentives are needed for them to change their activities to be more environmentally friendly. Although if you look at current practices abroad, the insurance industry actually reduces insurance cover incentives for activities that damage the environment. The role of sharia insurance in carbon trading not only includes financial protection, but can also help build sustainability and social responsibility in this sector. In the context of sharia insurance, transactions must comply with sharia principles, such as the prohibition of usury and immeasurable uncertainty (gharar) such as uncertainty in aspects of quality, quantity and price.